In-Utero SSRI and SNRI Exposure and the Risk of Long Term Adverse Mental and Educational Outcomes in Children: A Population-Based Retrospective Cohort Study Utilizing Linked Administrative Data. (2018) - Singal, Deepa; Chateau, Dan; Dahl, Matthew; Katz, Laurence; Ruth, Chelsea; Wall-Wieler, Elizabeth; Hanlon-Dearman, Ana; Brownell, Marni
No abstract available